2014
DOI: 10.5958/2231-6701.2014.01202.0
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Integrated Pest Management Practices in Production of Bt Cotton in Karimnagar District of Andhra Pradesh - A Case Study

Abstract: Integrated Pest Management in cotton production was demonstrated under Front Line Demonstration (FLD) in two villages in Karimnagar district of Andhra Pradesh during 2008-09 to 2010-11. The results revealed that IPM practices were superior in controlling aphids, mealy bug and Spodoptera as the incidence of these pests was significantly lower in the production of cotton. The activity of beneficial insects also improved in IPM fields when compared with non IPM fields. Seed cotton yield obtained was 16.6% higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In case of resource use efficiency, it was found that effective management of human labour and machine labour can facilitate in more profits in case of IPM technology. The results of the research were found similar and highly correlated to studies made at different corners of India [8], [9], [10], [11], [12], [13], [14], [15], [16].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In case of resource use efficiency, it was found that effective management of human labour and machine labour can facilitate in more profits in case of IPM technology. The results of the research were found similar and highly correlated to studies made at different corners of India [8], [9], [10], [11], [12], [13], [14], [15], [16].…”
Section: Resultssupporting
confidence: 77%
“…Higher net returns were obtained from integrated pest management in Bt cotton, as compared to recommended plant protection in Bt cotton (₹67676 and ₹55403/ha) and integrated pest management for non-Bt cotton (₹61155 and ₹43633/ha) also, for both consecutive seasons [9]. Under the front line demonstration of integrated pest management in cotton during 2008-09 to 2010-11 in two villages of Karimnagar district of Andhra Pradesh, IPM practices was found to be highly effective in managing aphids, spodoptera and mealy bugs, with better activity of beneficial insects in IPM fields, higher seed cotton yield (16.6 per cent), higher net returns (₹ 54217/ha in IPM, ₹ 40488/ha in non-IPM fields) and benefit to cost ratio (2.69 in IPM and 2.15 in non-IPM fields [10].…”
Section: Fig 1 Major Countries In Cotton Productionmentioning
confidence: 99%